Acoustic stimulation during slow wave sleep shows delayed effects on memory performance in older adults - Wunderlin, Marina; Zeller, Céline J.; Wicki, Korian; Nissen, Christoph; Züst, Marc A. (Frontiers in Sleep, 2024)
Introduction In young healthy adults, phase-locked acoustic stimulation (PLAS) during slow wave sleep (SWS) can boost over-night episodic memory consolidation. In older adults, evidence is scarce and available results are inconsistent, pointing toward reduced PLAS-effectiveness. We argue that multiple stimulation nights are required for effects to unfold in older individuals to compensate for age-related reductions in both SWS and memory performance. We test this assumption in a longitudinal within-subject design. Methods In a larger previous project, older adults participated in a three-night intervention receiving either real-PLAS (STIM group) or sham-PLAS (SHAM group). Encoding and immediate recall of face-occupation pairs was administered on the evening of the first intervention night (session one), with feedback-based retrievals ensuing on all following mornings and evenings across the intervention. To test for the benefit of the real-PLAS over sham-PLAS intervention within participants, 16 older adults [agemean: 68.9 (SD: 3.7)] were re-invited receiving the real-PLAS intervention exclusively. This resulted in a SHAMSTIM group (n = 9; T1: sham-PLAS intervention, T2: real-PLAS intervention) and a STIMSTIM group (n = 7; T1 and T2: real-PLAS intervention). Results While the STIMSTIM group exhibited highly similar responses during T1 and T2, the SHAMSTIM group exhibited a significantly higher increase in memory performance at T2 (real-PLAS) compared to T1 (sham-PLAS). These gains can be attributed to the late stages of the experiment, after three nights of real-PLAS, and remained stable when correcting for changes in baseline sleep quality (PSQI) and baseline cognitive ability (Montreal Cognitive Assessment) between T1 and T2. Conclusions We show that in older adults, PLAS-induced memory effects are delayed and manifest over the course of a three-night-PLAS intervention. Our results might explain the lack of effects in previous PLAS studies, where memory performance was solely assessed after a single night of PLAS.